Rural electrification chronicle 2006-2008. - Philippines National Electrification Administration (Quezon City National Electrification Administration, 2008)
Contains PDF files, PPT files and maps.
1. Foreword -- 2. National summary -- 3. NEA M-V-M & Credo -- 4. Philippine Map -- 5. Location maps and statistical profile of electric cooperatives -- 6. Other edu's -- 7. Tables & graphs -- 8. Organizational chart & edit board.
Keywords: Rural electrification -- Philippines